2010
DOI: 10.1007/s12010-010-9112-z
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of the Antibacterial Activity of Bacillus subtilis B38 Strain against Methicillin-Resistant Staphylococcus aureus

Abstract: When cultured in minimal growth medium, the B38 strain of Bacillus subtilis did not exhibit any antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) clinical isolate. Coculturing B38 strain with viable MRSA cells weakly increased antibacterial activity production (20 AU/ml). Addition of dead MRSA cells in a B38 culture, increased by 8-fold the B. subtilis strain antibacterial activity reaching 160 AU/ml against MRSA strain. This antibacterial activity recovered from cell-free super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These results indicated that, in the presence of the pathogen (MRSA ATCC 33742), strain PD9 produced more antimicrobial metabolites. The induction of antimicrobial metabolite in the presence of competing species or pathogens was also observed in related studies of B. subtilis B38 against MRSA [47] and soil bacterial isolates against E. coli and S. aureus [48]. From the MBC analysis, it was found that the CFS had bactericidal activity.…”
Section: Plos Onementioning
confidence: 58%
See 1 more Smart Citation
“…These results indicated that, in the presence of the pathogen (MRSA ATCC 33742), strain PD9 produced more antimicrobial metabolites. The induction of antimicrobial metabolite in the presence of competing species or pathogens was also observed in related studies of B. subtilis B38 against MRSA [47] and soil bacterial isolates against E. coli and S. aureus [48]. From the MBC analysis, it was found that the CFS had bactericidal activity.…”
Section: Plos Onementioning
confidence: 58%
“…The induction of antimicrobial metabolite in the presence of competing species or pathogens was also observed in related studies of B . subtilis B38 against MRSA [ 47 ] and soil bacterial isolates against E . coli and S .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that individual marine biofilm isolates can be induced to express increased activity against S. aureus when grown in the presence of spent culture media from S. aureus, or in co-culture with S. aureus (Burgess et al 1999;Kanagasabhapathy and Nagata 2008). Similarly, Bacillus subtillus has been reported to have inducible activity against S. aureus (Tabbene et al 2011), and marine epibiotic isolates to have inducible activity against Pseudomonas aeruginosa (Dusane et al 2011). These studies featured selected bacteria which were known antibiotic producers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the addition of Klebsiella weissii Br26 to fermentation supernatants at different growth stages resulted in a signi cant but not identical enhancement of its inhibitory activity, suggesting that the biosynthesis of bacteriocin can be self-induced in addition to receiving the in uence of the time of addition [50]. Similarly, the addition of further cell-free supernatant of Bacillus subtilis B38 increased its own antimicrobial activity by 8-fold to 160 AU/mL [51]. Summarizing the results of the above studies, it could be inferred that when the concentration of the inducing substance in the inducing supernatant reaches a certain threshold, the inducing effect appears; while when the inducing supernatant is added at the wrong time, the inducing effect does not occur.…”
Section: The Change Of Exo-metabolome On Plantaricin In Co-culturementioning
confidence: 99%